Electrochemical study on the effect of polar and non-polar extract of Artemisia vulgaris on the corrosion inhibition of mild-steel in an acidic medium. Issue 11 (8th March 2023) - Karki, Nabin; Neupane, Shova; Gupta, Dipak Kumar; Yadav, Amar Prasad
Abstract : A study of inhibition efficacy of Artemisia vulgaris by electrochemical methods. Abstract : Electrochemical methods were used to characterize the inhibition efficacy of the extract of the high-altitude plant Artemisia vulgaris as an environmentally acceptable inhibitor for mild steel in 1.0 M H2 SO4 . The Artemisia vulgaris was extracted in hexane and methanol separately and applied on mild steel (MS) as an inhibitor. A detailed electrochemical characterization such as potentiodynamic polarization, open circuit potential, and electrochemical impedance spectroscopy (EIS) was performed on the MS surface covered with the extract molecules. The hexane extracts adsorbed slower to the MS surface than the methanol extract, but both molecular extracts showed similar corrosion inhibition efficacies (IE). The IE for 1000 ppm extract in hexane and methanol was 73.10% and 91.99%, respectively, after 0.5 hour immersion of MS, whereas it was 98.79% and 96.73% in hexane and methanol extract after 24 hours of immersion of MS in acidic medium. The IE of the methanol extract increased with concentration. From the EIS analytical analysis, adsorption of inhibitor molecules on the charge transfer kinetics was confirmed. The potentiodynamic polarization showed a decrease in current density with the concentration of methanol extract without affecting the Tafel slopes. ATR-FTIR of the extract indicated the presence of the different functionalities in it. Adsorption of the extract molecules on the metal surface obeyed the Langmuir adsorption isotherm. The computed value of Δ G * implies that the adsorption is of mixed type. The formation of a protective film of inhibitor molecules on the MS surface was confirmed from EIS and using a scanning electron microscope. The adsorption mechanism based on the experimental data supported by the thermodynamic calculations is highlighted in this article.